Sequencing of 16S rRNA reveals a distinct salivary microbiome signature in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Behcet's disease (BD) is characterized by recurrent oro-genital ulcers, mucocutaneous lesions, and serious organ involvement. We investigated the salivary microbiome in BD using high-throughput sequencing of the 16S rRNA V4 region. Stimulated saliva samples were collected from 31 BD patients and 15 healthy controls, and in 9 BD patients, a second saliva sample was collected following dental and periodontal treatment. Sequence analysis identified a total of 908 operational taxonomic units (OTUs) present across all samples. Patients had a microbial community structure that is significantly less diverse than healthy controls. The most overabundant species in BD was Haemophilus parainfluenzae, while the most depleted included Alloprevotella rava and species in the genus Leptotrichia. Periodontal treatment improved oral health indices in BD but had no short-term effect on bacterial community structure. Neither the BD-associated genetic risk locus within the HLA-B/MICA region nor being on immunosuppressive medications explained the differences between patients and controls. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Behcet's disease; Microbiome; Sequencing; 16s rRNA; Genetics; Oral microbial diversity; GUT MICROBIOTA; PREVOTELLA-TANNERAE; BACTERIAL DIVERSITY; ORAL MICROBIOME; IDENTIFICATION; ASSOCIATION; HEALTH; COLONIZATION; BIOMARKERS; CAVITY